Numerical and experimental study of Stirling refrigerator coupling to convert thermal energy into cold energy - Ezatollah Hassanzadeh, M.A. Ehyaei, Saeed Jafari Mehrabadi, Arash Mohammadi, Hossein Mazaheri (Drugs and Cell Therapies in Hematology, 2021)
The main aim of this research was to experimentally investigate the two coupled identical ST500 gamma-type Stirling engines and convert thermal energy into cooling energy. The effective cooling is obtained in the cold engine using a new structure and two coupled Stirling engines at different temperatures and pressures, as well as the use of biomass fuel within the 4-8 bar average pressure range of the first engine hot source, the 1-4 bar average pressure range of the second engine cold source, and Stirling hot engine temperature range of 480-580 ºC. Furthermore, the Nlog code was used to validate the results. In doing tests, attempts were made to reach lower than 9% error results in different parts of an engine, including insulation, fluid leakage, belt losing, and measurement devices. According to the obtained results, an 8 bar increase in the average pressure range of the gas in the first engine hot source, a 1 bar reduction in the average pressure range of the gas in the second engine cold source, the increased temperature of the hot source up to 580 ºC, and the use of the light operating fluid, such as helium, will affect the generation of cooling up to -16 ºC.